Verbal Creativity Is Correlated With the Dynamic Reconfiguration of Brain Networks in the Resting State - Feng, Qiuyang; He, Li; Yang, Wenjing; Zhang, Yao; Wu, Xinran; Qiu, Jiang (Frontiers in Psychology, 2019)
Creativity is the foundation of human culture.All inventions and innovations in history rely upon us to break with the traditional thinking ,and create something novel. A number of neuroimaging studies have explored the neural mechanism of creativity. However, a majority of researches have focused only on the stationary functional connectivity in resting-state fMRI and task-related fMRI,neglecting the dynamic variation of brain networks. Here, we used dynamic network analysis to investigate the relation between the dynamic reorganization of brain networks and verbal creativity in 370 healthy subjects. We found that the integration of the left lingual gyrus and left middle temporal gyrus (MTG) in default mode network (DMN) and the integration of the DMN and cerebellum, frontoparietal task control network (FPTC)and auditory network (Aud) showed positive correlation with verbal creativity performance. In addition, the recruitment of the bilateral postcentral gyrus from the sensory/somatomotor network(SMN) and the recruitment of the SMN in general displayed a significant correlation with verbal creativity scores. Taken together, these results suggested that the dynamic reorganization among the brain networks involved in multiple cognitive processes,such as memory retrieval, imaginative process,cognitive control were important for verbalcreativity. These findings provided direct evidence that verbal creativity was related to the dynamic variation of brain mechanism during resting-state, extending past research on the neural mechanism of creativity. Meanwhile, this results bought about new perspectives for verbal creative training and rehabilitation training of depression